Cognitive recovery in patients with post-stroke subjective cognitive complaints - Ji, Shaozhen; Sun, Hong; Jin, Xianglan; Chen, Baoxin; Zhou, Jing; Zhao, Jiayi; Liang, Xiao; Shen, Wei; Zhang, Yunling; Chan, Piu (Frontiers in Neurology, 2022)
Background and purpose The objective cognitive trajectory in patients with post-stroke subjective cognitive complaints (SCC) over time remained unknown. We investigated cognitive outcomes in patients with SCC within one year after stroke, and determined factors associated with cognitive recovery. Methods This study included 599 patients with a clinical diagnosis of post-stroke SCC and evidence of cognitive deficits including Clinical Dementia Rating Scale (CDR) =0.5, Montreal Cognitive Assessment (MoCA) score < 26, and Mini–Mental State Examination score >17 (illiterate) or > 20 (primary school) or > 24 (junior school or above). Neuropsychological assessment was performed at baseline (2 weeks to 6 months after stroke) and six-month follow-up visit. Cognitive recovery was operationalized as unimpaired cognition (MoCA score≥26 and CDR=0) after six months. Factors associated with recovery were defined through logistic regression analysis. Results After six months, 583 patients completed the follow-up with 80 (13.72%) presenting cognitive recovery, among which, 22 (9.48%) cases reported SCC within 2 weeks after stroke, 6 (10%) at 15-30 days, 13 (15.12%) at 31-60 days, 10 (16.13%) at 61-90 days, 5 (10.42%) at 91-120 days, 9 (23.08%) at 121-150 days, and 15 (26.79%) at 151-180 days. Compared to those reported cognitive complaints at 151-180 days after stroke, patients with early post-stroke SCC had poorer cognitive recovery, which was only significant in individuals with high level of education. Male sex, higher baseline MoCA scores, coffee intake and thalamus lesions were independently associated with high chance of cognitive recovery. Conclusions Although post-stroke SCC contributes to persisting objective cognitive deficits, some patients presented cognitive recovery within one year after stroke. Patients with a high education level reporting SCC at earlier stage after stroke had poorer cognitive recovery. Male, higher baseline MoCA scores, coffee intake and thalamus lesions appear to independently predict cognitive recovery.